Poster: UAV-Assisted Cooperative Perception in Vehicular Network - Kim, Chang Kyung; Jeong, Junho; Lee, SuKyoung (Proceedings - International Conference on Network Protocols, 2025)
This paper proposes a UAV-assisted cooperative perception framework for vehicular networks, ensuring the timely transmission of image feature extraction results from vehicles to the RSU, thereby enabling cooperative perception such as HD map construction and object-level tracking in smart cities. We analyze the success probability that vehicles can complete image feature extraction and transmit the result before leaving the RSU's communication range with the assistance of UAVs. The simulation results demonstrate that the proposed algorithm outperforms benchmark schemes in terms of success probability.